Fostering children's creativity in preschool institutions - Đuranović, Marina (Array, 2020)
Alongside family, preschool institutions present the most important factor of preschool children’s growth and development. They are places where children live, grow, learn and play. The preschool institution’s curriculum has to be flexible, open, adjusted to children’s needs and abilities, and founded on creativity. Children’s creativity can be fostered and developed through all activities in preschool institutions: play, music activities, art activities, drama, kinesiological and many other activities. A significant role in fostering children’s creativity falls upon the preschool teachers who, in order to successfully develop creativity in children, need to be aware of its importance and themselves work in an environment that supports creativity. The goal of this work is to raise awareness about fostering and developing children’s creativity and creation since the earliest child’s age as one of eight key competences for lifelong education.